2013
DOI: 10.2169/internalmedicine.52.8572
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of the Circulating Cellular Adhesion Molecules ICAM-1, VCAM-1 and Endothelin-1 and the Flow-mediated Vasodilatation Values in Patients with Type 1 Diabetes Mellitus with Early-stage Diabetic Retinopathy

Abstract: Objective Endothelial dysfunction plays an important role in the development of diabetic retinopathy. The aim of this study was to evaluate endothelial dysfunction using different approaches in patients with type 1 diabete mellitus with early stages of diabetic retinopathy. For this purpose, we investigated the serum levels of cellular adhesion molecules, including intercellular adhesion molecule (ICAM-1), vascular cell adhesion molecule (VCAM-1) and endothelin-1 (ET-1), which have emerged as specific markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
5
21
1
4
Order By: Relevance
“…In a study of patients with T2DM, the sICAM-1 and sVCAM-1 concentrations were found to be higher in the study group. However, plasma sVCAM-1, but not sICAM-1, was independently associated with DKD, suggesting that sICAM-1 and sVCAM-1 may play different roles in the different stages of the same disease [19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of patients with T2DM, the sICAM-1 and sVCAM-1 concentrations were found to be higher in the study group. However, plasma sVCAM-1, but not sICAM-1, was independently associated with DKD, suggesting that sICAM-1 and sVCAM-1 may play different roles in the different stages of the same disease [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of ICAM-1 have been reported in the diabetic retina in the early stages of retinopathy, suggesting that ICAM-1 mediates the adhesion and transendothelial migration of circulating leukocytes through the retinal vessel walls, one of the earliest pathological changes observed in the course of the development of DR [19]. Further research has found plasma CD146 levels to be elevated at the early stage of diabetic complications [20].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the presence of retinopathy was not significantly associated with FMD responses. Similarly, Ugurlu et al 9 analysed FMD responses in patients with type 1 diabetes. Subjects with diabetes and no DR, diabetes and early DR and normal controls were compared, with no differences found in any of the markers of endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…FMD measurement is however operator dependent and may be affected by measurement-induced changes in systemic haemodynamics. Studies using FMD have thus far identified inconsistent relationships between DR and endothelial dysfunction, with some reporting reduced FMD in DR,1 6–8 and others reporting no relationship 3 9…”
Section: Introductionmentioning
confidence: 99%
“…The results of the studies in the group of diabetic patients with controlled disease revealed that its level was comparable to the control group and our results are in line with this observation. According to Ugurlu et al [23] endothelin serum concentration cannot be used to assess local imbalance of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%